2010
DOI: 10.20396/etd.v11i2.889
|View full text |Cite
|
Sign up to set email alerts
|

Imágenes cartográficas del mundo e imaginarios geográficos en la geografía escolar en Argentina

Abstract: Cartographic images, as well as other sort of images, offer different ways of visualizing and imagining the world. This type of images have an important place in visual culture: articles, summaries, advertisements and public presentations use them in order to show different phenomena. We propose to discuss the presence of one kind of cartographic image in schooling geography in Argentina. Finally, we attempt to point out the possibilities that are opened up with the introduction of other world’s cartographic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Hollman and Lois's study on the representation of geography in Billiken under Peronism highlights the new Peronist decrees rendered visible in the magazine, such as the 1946 decree prohibiting maps of the Argentine territory that failed to include the Antarctic section. 61 However, as their study does not consider Billiken before Peronism, it presents some of the material as a result of uniquely Peronist preoccupations, rather than Peronist reconfigurations of existing trends or commemorative dates. Billiken's showcasing of Argentina as both a country of outstanding natural beauty and a modern, industrialised nation with appropriate infrastructure predated and, indeed, succeeded Peronism.…”
Section: Billiken and The Segundo Plan Quinquenal (1953-1955)mentioning
confidence: 99%
“…Hollman and Lois's study on the representation of geography in Billiken under Peronism highlights the new Peronist decrees rendered visible in the magazine, such as the 1946 decree prohibiting maps of the Argentine territory that failed to include the Antarctic section. 61 However, as their study does not consider Billiken before Peronism, it presents some of the material as a result of uniquely Peronist preoccupations, rather than Peronist reconfigurations of existing trends or commemorative dates. Billiken's showcasing of Argentina as both a country of outstanding natural beauty and a modern, industrialised nation with appropriate infrastructure predated and, indeed, succeeded Peronism.…”
Section: Billiken and The Segundo Plan Quinquenal (1953-1955)mentioning
confidence: 99%
“…Previous studies in Argentina have suggested that despite the greater availability and circulation of images, both teachers and students do experience a surprising visual homogeneity when asked to choose images of the contemporary period (Dussel, 2009;Hollman, 2010). Assuming that the visual order constructed by students was evidence of a hegemonic mode of visualizing of Latin America, the challenge was to imagine a different starting point for the following semesters.…”
Section: Teaching To Conceptualize a Visualized Latin Americamentioning
confidence: 99%
“…Research on the use of images in teaching the subject of geography is sparse in Argentina, and there are only a few published studies on this topic (Hollman, 2010(Hollman, , 2011(Hollman, , 2013. However, based on the author's learning and teaching experience some initial conclusions will be put forward.…”
Section: Introductionmentioning
confidence: 99%
“…El formato impreso de tipo planisferio 1 constituye una mediación en el proceso de enseñanza de los conceptos relacionados con la cartografía, además de ser una herramienta para la comprensión de categorías asociadas a disciplinas como la historia y la economía. El uso de mapas impresos de gran formato, así como de textos especializados en la recopilación de mapas temáticos, conocidos como Atlas, ha estado presente en las aulas de instituciones educativas escolares determinando, en buena parte, los imaginarios de estudiantes frente a la forma de entender la realidad geográfica, espacial o terrestre (Hollman, 2010).…”
Section: Introductionunclassified